Crunch time : how to be your best when it matters most - Peterson, Rick, 1954 October 30-; Hoekstra, Judd, 1970- (Business professional collection, 2017)
With behind-the-scenes examples from some of the top names in sports and business, this book offers six reframing strategies to help you see a pressure situation with a new perspective so that it shifts from a threat that can make you panic to an opportunity for you to shine. --